2018
DOI: 10.1071/rd17352
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid transporter expression in the endometrium and conceptus membranes during early equine pregnancy

Abstract: Maternally derived amino acids (AA) are essential for early conceptus development, and specific transporters enhance histotrophic AA content during early ruminant pregnancy. In the present study we investigated AA transporter expression in early equine conceptuses and endometrium, during normal pregnancy and after induction of embryo-uterus asynchrony. 'Normal' conceptuses and endometrium were recovered on Days 7, 14, 21 and 28 after ovulation. To investigate asynchrony, Day 8 embryos were transferred to recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…We previously reported that negatively asynchronous ET delays conceptus development at the level of the whole conceptus and for selected genes known to exhibit parent-of-origin imprinting [40] or related to nutrient uptake [41,42]; the retardation in development presumably results from differences in histotroph composition due to the reduced duration of endometrial exposure to P4 prior to embryo introduction. The transcriptome comparisons performed between conceptus membranes at the different stages (D14-syn/asyn; D19-syn/asyn) indicated distinct profiles of DEGs, but gene ontology analysis revealed similar overrepresented categories to those reported previously between day 10, 12 and 14 compared to day 8 conceptuses by Klein and Troedsson [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that negatively asynchronous ET delays conceptus development at the level of the whole conceptus and for selected genes known to exhibit parent-of-origin imprinting [40] or related to nutrient uptake [41,42]; the retardation in development presumably results from differences in histotroph composition due to the reduced duration of endometrial exposure to P4 prior to embryo introduction. The transcriptome comparisons performed between conceptus membranes at the different stages (D14-syn/asyn; D19-syn/asyn) indicated distinct profiles of DEGs, but gene ontology analysis revealed similar overrepresented categories to those reported previously between day 10, 12 and 14 compared to day 8 conceptuses by Klein and Troedsson [19].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the embryonic disc (day 14) and embryo proper (day 19) are smaller and less well developed in conceptuses resulting after transfer of day 8 horse embryos into a 5-day negatively asynchronous recipient compared to a synchronous recipient [40]. In addition, the pregnancy stage-related upregulation in mRNA expression for a range of imprinted genes, glucose and amino acid transporters is delayed in conceptuses that develop in a negatively asynchronous uterus [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that negatively asynchronous ET delays conceptus development at the level of the whole conceptus and for selected genes known to exhibit parent-of-origin imprinting [38] or related to nutrient uptake [39,40]; the retardation in development presumably results from differences in histotroph composition due to the reduced duration of endometrial exposure to P4 prior to embryo introduction. The transcriptome comparisons performed between conceptus membranes at the different stages (D14-syn/asyn; D19-syn/asyn) indicated distinct profiles of DEGs, but gene ontology analysis revealed similar overrepresented categories to those reported previously between day 10, 12 and 14 compared to day 8 conceptuses by Klein and Troedsson [19].…”
Section: Discussionmentioning
confidence: 99%
“…All animal procedures were approved by Utrecht University's Animal Experimentation Committee (permit number 2012.III.02.020). Material for the transcriptomic analysis was collected from 22 warmblood mares, and used in previous studies [38][39][40]; material for the in vitro experiments was harvested from an additional 5 mares. Mares were between 4 and 15 years of age and maintained on pasture with ad libitum access to grass, hay and water.…”
Section: Animals and Tissue Collectionmentioning
confidence: 99%
See 1 more Smart Citation